Gothic queer culture : marginalized communities and the ghosts of insidious trauma - Westengard, Laura (Expanding frontiers., 2019)
In Gothic Queer Culture, Laura Westengard proposes that contemporary U.S. queer culture is gothic at its core. Using interdisciplinary cultural studies to examine the gothicism in queer art, literature, and thought - including ghosts embedded in queer theory, shadowy crypts in lesbian pulp fiction, monstrosity and cannibalism in AIDS poetry, and sadomasochism in queer performance - Westengard argues that during the twentieth and twenty-first centuries a queer culture has emerged that challenges and responds to traumatic marginalization by creating a distinctly gothic aesthetic. Gothic Queer Culture examines the material effects of marginalization, exclusion, and violence and explains why discourse around the complexities of genders and sexualities repeatedly returns to the gothic. Westengard places this queer knowledge production within a larger framework of gothic queer culture, which inherently includes theoretical texts, art, literature, performance, and popular culture. By analyzing queer knowledge production alongside other forms of queer culture, Gothic Queer Culture enters into the most current conversations on the state of gender and sexuality, especially debates surrounding negativity, anti-relationalism, assimilation, and neoliberalism. It provides a framework for understanding these debates in the context of a distinctly gothic cultural mode that acknowledges violence and insidious trauma, depathologizes the association between trauma and queerness, and offers a rich counterhegemonic cultural aesthetic through the circulation of gothic tropes.